2019
DOI: 10.1002/qua.25996
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carbon‐carbon bonding in small hydrocarbons and dicarbon using dynamic orbital forces: Bond energies and sigma/pi partition. Comparison with sila compounds

Abstract: The CC bonding is analyzed using dynamic orbital forces (DOF) in the series cyclopropane-ethane-benzene-ethylene-acetylene. The sum Σ(DOF) t of the DOF over occupied molecular orbitals (MOs) is found linearly correlated to bond energies and thus can be used as a tool for determination of CC bond strength. A partition of bonding into σ and π components indicates a weakening of the σ bonding along the series, mainly due to the decrease of the bonding character of the highest σ MO. For C 2 molecule, Σ(DOF) t was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In particular, their DOFs are consistent with the bond lengthening in N 2 + and the bond shortening in CO + , with respect to the neutral species. The σ g + LUMO of C 2 , in its dominant configuration, also belongs to the same “inverted” type, with a DOF of −0.003 a.u …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, their DOFs are consistent with the bond lengthening in N 2 + and the bond shortening in CO + , with respect to the neutral species. The σ g + LUMO of C 2 , in its dominant configuration, also belongs to the same “inverted” type, with a DOF of −0.003 a.u …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been found that the C−C bond energy in a series of hydrocarbons is linearly correlated to Σ. Moreover the σ/π partition of the total bonding was obtained by comparing the sums Σ σ and Σ π over occupied σ and π MOs, respectively . These results require that the system is essentially mono‐configurational.…”
Section: Resultsmentioning
confidence: 99%
“…As an extension of this model, the DOFs with respect to a given interatomic distance are summed over all the MOs (ϕ i ) of a molecule, and the result Σ(DOF i ) is considered as the central quantity that determines the nature and strength of a particular bond. A large positive Σ(DOF i ) corresponds to a strong bond, while a negative Σ(DOF i ) signifies a repulsive interaction . This method was recently applied to a series of hydrocarbons and a linear correlation was found between the CC bonding energies and the CC Σ(DOF i ) …”
Section: Methodsmentioning
confidence: 99%
“…Moreover the / partition of the total bonding was obtained by comparing the sums   and   over occupied  and  MOs, respectively. 18 These results require that the system is essentially mono-configurational. It is indeed the case for propellane as evidenced by the fact that its CASPT2 and MP2 energies differ by less than 0.01 a.u.…”
Section: Evaluation Of Bond Energies and / Partitionmentioning
confidence: 99%
“…The  g + LUMO of C 2 , in its dominant configuration, also belongs to the same "inverted" type, with a DOF of -0.003 a.u. 18 In order to further delve on the nature of these orbitals, we have also analyzed [1.1.1]bicyclopentane 2. The MOs of 2 mainly differ from the preceding ones by the HOMO a" 2 , which is strongly antibonding, resulting from the 4-electron interaction of the  orbitals of both C-H bonds at a very short CC distance (ca.…”
mentioning
confidence: 99%